2016
DOI: 10.5194/soil-2-71-2016
|View full text |Cite
|
Sign up to set email alerts
|

Potential effects of vinasse as a soil amendment to control runoff and soil loss

Abstract: Abstract. Application of organic materials are well known as environmental practices in soil restoration, preserving soil organic matter and recovering degraded soils of arid and semiarid lands. Therefore, the present research focused on evaluating the effectiveness of vinasse, a byproduct mainly of the sugar-ethanol industry, on soil conservation under simulated rainfall. Vinasse can be recycled as a soil amendment due to its organic matter content. Accordingly, the laboratory experiments were conducted by us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 44 publications
1
14
0
1
Order By: Relevance
“…It should be noted that the active agricultural soil had higher infiltration rates than the soils abandoned for 2, 5 and 10 years, although after the second year of abandonment there was a clear increase in the steady-state infiltration rate with increased time of abandonment. It is well known that management determines the infiltration rates in agricultural soils (Wang et al, 2015;Shi et al, 2015;Hazbavi and Sadeghi, 2016) and that as we found at the Valencia study site, there was a clear influence of vegetation on soil properties due to the improvement of soil quality by litter and root additions (de Boever et al, 2014) and an impact on runoff generation and hydraulics (Zhao et al, 2015). This positive impact of vegetation can be seen in agricultural soils, but also in restored mine soils and landfills (Cassinari et al, 2015;Thomas et al, 2015).…”
Section: Soil Hydrology and Erosion After Abandonmentsupporting
confidence: 59%
“…It should be noted that the active agricultural soil had higher infiltration rates than the soils abandoned for 2, 5 and 10 years, although after the second year of abandonment there was a clear increase in the steady-state infiltration rate with increased time of abandonment. It is well known that management determines the infiltration rates in agricultural soils (Wang et al, 2015;Shi et al, 2015;Hazbavi and Sadeghi, 2016) and that as we found at the Valencia study site, there was a clear influence of vegetation on soil properties due to the improvement of soil quality by litter and root additions (de Boever et al, 2014) and an impact on runoff generation and hydraulics (Zhao et al, 2015). This positive impact of vegetation can be seen in agricultural soils, but also in restored mine soils and landfills (Cassinari et al, 2015;Thomas et al, 2015).…”
Section: Soil Hydrology and Erosion After Abandonmentsupporting
confidence: 59%
“…The sesbania brown manuring in DSAR significantly reduced the density and dry biomass of weeds (Table II), probably because of decreased availability of sunlight to the germinating weed seeds and weed plants, which inhibited the weed seed germination and photosynthesis in weeds (Chauhan & Mahajan, 2014;Hazbavi & Sadeghi, 2016). Being a legume, sesbania is more efficient in utilizing limited resources than are weeds.…”
Section: Discussionmentioning
confidence: 99%
“…In Iran, although various attempts of land rehabilitation have been attempted using different soil amendments including organic (e.g., Behzadfar et al, ; Hazbavi & Sadeghi, ; Jourgholami, Labelle, & Feghhi, ; Kavian et al, ; Khalili Moghadam, Jamili, Nadian, & Shahbazi, ; Kia Kianian, Asgari, Bahadori, Resources, & Agricultural, ; Masumian, Naghdi, Zenner, Nikooy, & Lotfalian, ; Sadeghi, Hazbavi, & Kiani‐Harchegani, ) and inorganic (e.g., Emami & Astaraei, ; Hazbavi et al, ; Kia Kianian et al, ; Padidar et al, ; Safari, Kavian, Parsakhoo, Saleh, & Jordán, ) soil amendments under different conditions, very limited research (Gholami, Khaledi Darvishan, & Kavian, ; Jourgholami & Etehadi Abari, ) has been done on reducing runoff and soil erosion control using wood‐based mulches. Importantly, no study has examined reducing runoff, soil loss and sediment concentration behavior using different wood lengths and coverages.…”
Section: Introductionmentioning
confidence: 99%